Investigation of solid waste characteristics in field-scale landfill test cells - Top, S.; Akkaya, G. K.; Demir, A.; Yildiz, S.; Balahorli, V; Aykut, N. O.; Bilgili, M. S. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2019)
This paper presents the results of an experimental study carried out in field-scale test cells in order to determine the effect of aeration and leachate recirculation on waste decomposition rate, solid waste characteristics, landfill gas composition and settlement in the landfill body. Four landfill test cells with the dimensions of 20 m x 40 m x 5 m were constructed in Komurcuoda Sanitary Landfill, Istanbul. Solid wastes representing Istanbul Asian side waste characteristics were landfilled in the test cells and they were operated simulating anaerobic (AN1), leachate recirculated anaerobic (AN2), semi-aerobic (A1) and aerobic landfilling (A2) methods. Alternative landfilling methods for accelerating solid waste stabilization in landfills were investigated by means of solid waste characteristics (elemental analysis, pH, moisture content, TOC, TKN, C/N ratio, volatile solid content (VS), biochemical methane potential (BMP), and stability index (SI) analysis), landfill gas components (CH4, CO2, O-2, and H2S), temperature variations in landfill body, and landfill settlement. The study indicated that aeration and leachate recirculation accelerate biodegradation rate. Higher rates of MSW biodegradation eventually provide reduction in the contaminant life span of the landfill by achieving a high waste volume reduction in a relatively short duration than anaerobic test cells, decrease the cost of long term monitoring incurred with post-closure of landfill sites. In case of impossibility of aerobic landfilling based on the results of the cost benefit analysis, it was stated out that semi-aerobic landfilling technology is also a viable method in shortening the stabilization time and accelerating the landfill gas production.
Keywords: Aerobic landfill; anaerobic landfill; semi-aerobic landfill; leachate recirculation; landfill gas composition; settlement; NITROGEN REMOVAL; REFUSE DECOMPOSITION; BIOGAS PRODUCTION; AERATION; DEGRADATION; MANAGEMENT; DESIGN; Environmental Sciences & Ecology